A review of photoelectrochemical water oxidation using hematite photoanode - Bodro, Odilia Galuh Ismoyo; Maulana, Ilham Aksan (Environmental and Materials, 2024)
Background: The sun, as an abundant and renewable energy source, provides a sustainable alternative to fossil fuels, which contribute significantly to CO₂ emissions and global warming. With CO₂ emissions surpassing 35 billion tons in 2023, the need for clean energy solutions has become increasingly urgent. Solar energy utilization includes photoelectrochemical (PEC) water splitting, where hematite is widely recognized as an efficient photoanode material due to its availability, stability, and favorable band gap for visible light absorption. However, hematite faces challenges such as poor conductivity, surface recombination, and slow oxygen evolution reaction (OER) kinetics, which limit its performance. Methods: This review examines various strategies to enhance hematite photoanode performance for PEC water splitting. The study explores three key approaches: (1) using three-dimensional conductive substrates with high surface area to facilitate heterojunction formation, (2) doping with tetravalent metal ions (e.g., Ti⁴⁺) to improve conductivity and charge carrier density, and (3) integrating Bi₂WO₆ with hematite to enhance charge separation and photoelectrochemical efficiency. The hydrothermal method was applied for hematite fabrication due to its feasibility, cost-effectiveness, and scalability. Findings: The analysis highlights the effectiveness of each strategy in overcoming hematite’s inherent limitations. The use of 3D conductive substrates improves electron transport and surface reaction sites, while Ti⁴⁺ doping enhances charge carrier density and conductivity. Conclusion: Hematite remains a promising photoanode material for PEC water splitting, but its limitations must be addressed to maximize efficiency. The combination of 3D conductive substrates, metal ion doping, and Bi₂WO₆ integration has shown potential in improving hematite’s photoelectrochemical performance. Novelty/Originality of this article: This review provides a comprehensive analysis of hematite performance enhancement strategies, focusing on the synergistic effects of 3D conductive substrates, Ti⁴⁺ doping, and Bi₂WO₆ integration.